Codimension two and three bifurcations of a predator–prey system with group defense and prey refuge - Liu, Xia; Wang, Jinling (Nonlinear Analysis: Modelling and Control, 2015)
A predator–prey system with nonmonotonic functional response and prey refuge is considered. We mainly obtain that the system has the bifurcations of cusp-type codimension two and three, these illustrate that the dynamic behaviors of the model with prey refuge will become more complicated than the system with no refuge.